Application of individual mathematical models of aviation angines’ functioning for control of maintenance of stocks of aircrafts’ one-type powerplants - Королев, П. В. (Proceedings of National Aviation University (archive), 1999)
An approach to organization of control of maintenance of stocks of aircrafts’ one-type power- plants based on the application of individual mathematical models of aviation engines’ functioning is proposed. The procedures for forming individual models and for their using for solution of three groups of technical tasks of control are considered